Extending product affordances to user manuals - Pavel, Nenad; Zitkus, Emilene [UNESP] (My University, 2017)
The aim of this study is to provide general guidelines on methods for designing user manuals. The goal is to illustrate the dependencies between product affordances, semantics, and user instruction. The study incorporates task-based reflective interviews with product design professionals who were charged with redesigning a manual for a product. The article emphasizes the application of a pedagogical instructional design (PID) approach to user manuals in which users aim to construct the meanings of a product and incorporate these into living practices.
Keywords: Affordance; Instructional design; User manuals